Analysis of Factors Associated With Recurrence of Early-Stage Endometrial Carcinoma and Atypical Endometrial Hyperplasia in Infertile Women After In Vitro Fertilization Treatment - Guo, Yaxing; Zong, Xuan; Li, Hongzhen; Qiao, Jie (Frontiers in Oncology, 2022)
Purpose: To explore the relationship between different artificial reproductive treatment (ART) strategies and tumor outcomes, by analyzing clinical data of patients with endometrial carcinoma (EC) and atypical endometrial hyperplasia (AEH). Methods: This retrospective study was performed in a tertiary hospital. Patients (n=131) with EC or AEH, who underwent in vitro fertilization (IVF) /intracytoplasmic sperm injection (ICSI) treatment between June 2010 and June 2021, were divided into a recurrence group and a non-recurrence group. Clinical characteristics and tumor outcomes were assessed. Results: 131 patients were followed up for 4-132 months; 33 patients had recurrence, the recurrence rate was 25.2%, 3-year recurrence-free survival (RFS) rate was 83.2±3.4%, and the 5-year RFS rate was 72.9±4.4%. Factors including the frequency of controlled ovarian stimulation (COS), the times of embryo transferred, the basal estradiol (E2) level, the total amount of gonadotropin (Gn) used, and the total number of days of Gn used had no significant effect on the recurrence of tumor lesions (p=0.522, 0.994, 0.553, 0.707, and 0.587, respectively). Histology type (HR: 4.92, 95%CI: 4.20-10.11, p ＜0.001) and successful/un successful live birth (HR: 0.30, 95%CI: 0.14-0.66, p=0.003) were independent factors of recurrence. Twenty-two of the 82 patients who received a single COS had recurrence. Different COS protocols and serum E2 levels on the trigger day had no significant effect on recurrence (p=0.738, 0.495). Conclusions: The degree at which an endometrial lesion progresses into carcinoma is a key factor affecting the recurrence of EC/AEH in patients after IVF/ICSI treatment, and successful live birth is a protective factor for the recurrence of endometrial lesions. Different COS protocols and COS frequencies, as well as the different doses and duration of Gn used during ART did not affect the recurrence of endometrial lesions.